Bilinguals, Monolinguals and their Choices of Metacognitive Strategies in Reading, Writing, Listening and Speaking - Falla-Wood, Julia; Varghese, Keciya (Advances in Social Sciences Research Journal, 2020)
The purpose of this explorative study is to compare the choices of metacognitive strategies made by bilinguals and monolinguals in reading, writing, listening, and speaking. Kovelman, Baker & Petitto (2008) compare bilingual and monolingual brains and observe that there is a differential activation in the syntactic process between bilinguals and monolinguals. Could there be a difference between monolinguals and bilinguals in the choice of metacognitive strategies too? The data, collected in three private institutions, one in Quebec, and two in Alberta, consists of 144 students, 72 monolinguals, and 72 bilinguals. The instrument of research is a questionnaire. The results of this study show that 63.8% of all participants are unaware of the concept of metacognition. This lack of awareness is found not only in high school students but also in senior university students. In the category of bilinguals, the students acknowledge being bilinguals, but the percentage of those who feel comfortable in both languages is only 47.2%. Regarding the choices of metacognitive strategies, there are more similarities than differences between bilinguals and monolinguals. The implications of these results could lead educators to be intentional in bringing awareness of the concept of metacognition in a more efficient manner. Further research is needed to determine if the choice of specific metacognitive strategies would improve the four language skills.